Biomanagement of the burrowing nematode (Radopholus similis) in black pepper - Ravichandra, N. G.; Kavitha, T. R. (Annals of Agricultural Research, 2022)
Several bioagents were applied during the initiation of Kharif (June) around each pepper vine basin for the management of Radopholus similis in farmers garden. Nematode population was less in neem cake @200g/ vine (May/June) + P. fluorescens @15g/vine (May/June & Oct/Nov) application followed by neem cake @200g/ vine (May/June) + AMF @15g/vine (May/June & Oct/Nov) combined application. In roots, least number of nematodes were observed in neem cake @200g/vine (May/June) + AMF @15g/vine (May/June & Oct/Nov) combined application followed by neem cake @200g/vine (May/June) + P. fluorescens @15g/vine (May/June & Oct/Nov) application. Maximum yield was recorded in neem cake @ 200g/vine (May/June) + P. fluorescens @15g/vine (May/June & Oct/Nov) application which was on par with neem cake @200g/vine (May/June) + AMF @15g/vine (May/June & Oct/Nov) combined application. Application of neem cake @200g/vine (May/ June) + P. fluorescens @15g/vine (May/June & Oct/Nov) effectively managed the nematode population and also increased the yield by 32 per cent.